Does preoperative anal physiology testing or ultrasonography predict clinical outcome with sacral neuromodulation for fecal incontinence?. Issue 11 (November 2015) - Quezada, Yarini; Whiteside, James; Rice, Tracy; Karram, Mickey; Rafferty, Janice; Paquette, Ian
Abstract Introduction and hypothesis To determine the value of preoperative anal physiology testing and transanal ultrasonography in predicting clinical response to sacral neuromodulation for fecal incontinence. Methods We report a retrospective study of all patients treated with sacral neuromodulation for fecal incontinence in a single practice between 2011 and 2014 was performed. Patient demographics included age, gender, comorbidities, presence of an ultrasound-defined external sphincter defect, and history of prior anal sphincter repair. Cleveland Clinic Florida (CCF) scores were used to assess the severity of fecal incontinence at baseline, and at 3, 6 and 12 months. Pearson's correlation coefficient was used to evaluate the relationship between preoperative physiology testing and ultrasonography and patient outcome. Results Sacral neuromodulation was trialed in 60 patients, of whom 31 had anorectal physiology testing and 29 did not. Patients who were tested were younger (60.9 vs. 71.4 years, p  = 0.013) and more likely to have had a prior overlapping sphincteroplasty (40.5 % vs. 15 %, p  = 0.043). Among patients who progressed to complete system implantation, CCF scores at 3 and 12 months were similar whether they had physiology testing or not. Likewise, patient outcome did not correlate with the finding of an ultrasound-defined external sphincter defect. Pearson's correlation coefficient was used to evaluate the relationship between the test results and the 3-month CCF scores. CCF scores 3 months after full system implantation did not correlate with the presence or size of an external sphincter defect, resting or squeeze pressure, pudendal nerve terminal motor latency, rectoanal inhibitory reflex, or minimum detectable volume. Conclusions Anal physiology testing and ultrasonography were not predictive of clinical outcomes among patients treated with sacral neuromodulation for fecal incontinence.